THE LOGIC OF LAW: POST-REALITY AS A NEW LEGAL ONTOLOGY - Banakh, Serhiy; Kovalchuk, Olha (Актуальні проблеми правознавства, 2026)
Every previous era of social transformation adapted legal categories without touching the ontological foundations of law itself. Today, the picture has changed fundamentally: the latest digital technologies (artificial intelligence, blockchain, augmented reality, decentralized networks) do not merely complicate social relations but alter the very nature of social space, subjectivity, and time. Classical legal ontology, shaped during the Enlightenment, proves incapable of encompassing relations that genuinely exist yet fall outside any of the available legal categories. This gives rise to the phenomenon that the article proposes to define as the «legal vacuum of post-reality». The study aims to conceptualize «post-reality» as an independent ontological category, to demarcate it from related concepts (Baudrillard’s hyperreality, Barlow’s cyberspace, Latour’s actor-network theory), and to establish the theoretical groundings of a novel legal ontology able to confront the challenges of the post-real environment. The methodological basis comprises ontological analysis combined with philosophical-legal synthesis, conceptual analysis, structural comparison, and legal modelling. The study establishes that post-reality is defined by four interrelated characteristics: the simultaneous coexistence of physical and digital spaces as a single social environment; the operation of algorithmic systems at a pace fundamentally incompatible with legal procedures; the delegation of legally significant actions to autonomous algorithmic agents; and the nullification of territorial attachment as the basis for determining applicable law. Collectively, these features undermine four postulates of classical legal ontology: spatial monism, the personalism of legal subjectivity, causal determinism, and temporal linearity. The article proposes: a concept of spatially neutral jurisdiction grounded in the personal connection between a subject and a legal order; a hybrid model of legal personality combining limited subjectivity of algorithmic agents with the subsidiary liability of human subjects; and a dual-vector approach to temporal incompatibility through the interplay of legal and technological adaptation.